Digital twin of end-of-life process-chains for a circular economy adapted product design – A case study on PET bottles - Mangers, Jeff; Amne Elahi, Mahdi; Plapper, Peter (Journal of cleaner production, 2023)
The concept of Circular Economy (CE) is gaining increasing attention as an indispensable renewal of linear economy without neglecting sustainable development goals. Closing resource loops and keeping resources in the system at the highest level of use for as long as possible are cited as the main goals of CE. However, due to missing information exchange, the lack of consistency between the existing end-of-life (EOL) infrastructure and the respective product designs hinders a successful circularity of resources. This research presents a method to collect, process, and apply EOL process data to provide the beginning-of-life (BOL) with important EOL-knowledge through a CE-adapted product design assessment. EOL-data is collected using a Circular Value Stream Mapping (C-VSM), EOL-information is processed using a digital state flow representation, and EOL-knowledge is applied by providing a decision-support tool for product designers in the context of a PET bottle case study in Luxembourg. The goal is to anticipate a circular flow of resources by reflectively aligning product design with the relevant EOL infrastructure. In contrast to the linear economy, the developed method makes it possible to consider not only the requirements of users but also the actual end users, the EOL process chains, when designing products.